(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate the effect of edible coatings based on starch and casein on the guavas physicochemical characteristics. The treatments were: Control (without edible coating); A (starch edible coating); AC (starch + casein edible coating); C (casein edible coating). The guavas were analyzed for weight loss, total titable acidity, total soluble solids, vitamin C and colorimetry. Starch edible coating (A) obtained lower weight loss (10,65%). The treatments A and C conserved initial total soluble solids levels. All edible coatings were efficients in ATT conservation. Starch and casein edible coating (AC) obtained less yellowing of guavas.